2007
DOI: 10.1063/1.2746949
|View full text |Cite|
|
Sign up to set email alerts
|

Ferroelectric and pyroelectric properties of highly (110)-oriented Pb(Zr0.40Ti0.60)O3 thin films grown on Pt∕LaNiO3∕SiO2∕Si substrates

Abstract: Articles you may be interested inElectric field modulation of magnetism and electric properties in La-Ca-MnO3/Pb(Zr0.52Ti0.48)O3 magnetoelectric laminate J. Appl. Phys. 113, 17C712 (2013); 10.1063/1.4795871 Erratum: Ferroelectric and pyroelectric properties of highly (110)-oriented Pb ( Zr 0.40 Ti 0.60 ) O 3 thin films grown on Pt ∕ La Ni O 3 ∕ Si O 2 ∕ Si substrates [Appl. Phys. Lett.90, 232908 (2007)] Appl. Phys. Lett. 91, 069901 (2007); 10.1063/1.2767970 Structure and properties of W O 3 -doped Pb 0.97 La 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…In Table I, we summarize the typical room temperature pyroelectric coefficients of polycrystalline PZT thin films on Si or metallized Si substrates for Ti-rich compositions. 13,[32][33][34][35][36][37][38][39][40][41][42][43][44][45] Specific details corresponding to the Ti composition, synthesis method, processing temperatures, film thickness, and texture are provided in this summary. Table I …”
Section: Introductionmentioning
confidence: 99%
“…In Table I, we summarize the typical room temperature pyroelectric coefficients of polycrystalline PZT thin films on Si or metallized Si substrates for Ti-rich compositions. 13,[32][33][34][35][36][37][38][39][40][41][42][43][44][45] Specific details corresponding to the Ti composition, synthesis method, processing temperatures, film thickness, and texture are provided in this summary. Table I …”
Section: Introductionmentioning
confidence: 99%
“…The pyroelectric coefficient p 3 of 3 Â 10 À 4 C=m 2 K in Pb Zr 0:4 Ti 0:6 ð Þ O 3 thin film is smaller than that of the experimental measurements, e.g. p 3 ¼ 7:8 Â10 À 3 C=m 2 K and p 3 ¼ 9 Â 10 À 3 C=m 2 K for (110) oriented Pb Zr 0:4 Ti 0:6 ð Þ O 3 thin films grown on Pt=LaNiO 3 =SiO 2 =Si and Pt=LiNiO 3 =Al 2 O 3 =Si substrates respectively [14,15].…”
Section: Resultsmentioning
confidence: 95%
“…The pyroelectric coefficient of 4:8 Â 10 À 4 C=m 2 K was observed at room temperature because of the high crystalline quality of the film. However, the excellent pyroelectric coefficient of 7:8 Â 10 À 4 C=m 2 K was found in highly (110) oriented PbðZr 0:4 Ti 0:6 ÞO 3 thin films which were prepared on (110) preferred Pt bottom electrodes [14,15]. Furthermore, it is expected that the dielectric and pyroelectric coefficient can be improved in (110) oriented PbðZr 0:5 Ti 0:5 ÞO 3 thin films.…”
Section: Introductionmentioning
confidence: 96%
“…Clearly, it could be found that larger dielectric tunability was obtained for films deposited at 300 C, which was contributed to its larger dielectric constant. Generally speaking, larger dielectric constant usually led to higher tunability [19]. The e r -E curves of PMN-PT 90/ 10 thin films deposited at 300 C with different thicknesses are showed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, LaNiO 3 (LNO) film was used as the bottom electrodes due to its good metallic conductivity, and also was served as an effective surface for the preferred growth of the ferroelectric thin films [17][18][19][20]. 250-nm-thick LNO layers with (100)-preferred orientation were first deposited at 550 C on silicon substrate by RF magnetron sputtering.…”
Section: Methodsmentioning
confidence: 99%